Short-term outcomes of a multicentre randomized clinical trial comparing laparoscopic pylorus-preserving gastrectomy with laparoscopic distal gastrectomy for gastric cancer (the KLASS-04 trial). Issue 9 (6th September 2021) - Park, D. J.; Kim, Y.-W.; Yang, H.-K.; Ryu, K. W.; Han, S.-U.; Kim, H.-H.; Hyung, W.-J.; Park, J. H.; Suh, Y.-S.; Kwon, O. K.; Yoon, H. M.; Kim, W.; et al.
Abstract: Background: There remain concerns about the safety and functional benefit of laparoscopic pylorus-preserving gastrectomy (LPPG) compared with laparoscopic distal gastrectomy (LDG). This study evaluated short-term outcomes of a randomized clinical trial (RCT) comparing LPPG with LDG for gastric cancer. Methods: The Korean Laparoendoscopic Gastrointestinal Surgery Study (KLASS)-04 trial was an investigator-initiated, open-label, parallel-assigned, superiority, multicentre RCT in Korea. Patients with cT1N0M0 cancer located in the middle third of the stomach at least 5 cm from the pylorus were randomized to undergo LPPG or LDG. Participants, care givers and those assessing the outcomes were not blinded to group assignment. Outcomes were 30-day postoperative morbidity rate and death at 90 days. Results: Some 256 patients from nine institutions were randomized (LPPG 129 patients, LDG 127 patients) between July 2015 and July 2017 and outcomes for 253 patients were analysed. Postoperative complications within 30 days were seen in 19.3 and 15.5 per cent in the LPPG and LDG groups respectively ( P  =   0·419). Postoperative pyloric stenosis was observed in nine (7.2 per cent) and two (1·5 per cent) patients in the LPPG and LDG groups ( P  =   0·026) respectively. In multivariable analysis higher BMI was a risk factor for postoperative complications (odds ratio 1·17, 95 per cent c.i. 1·04 to 1·32; P  =   0·011). Death at 90 days was zero in both groups. Conclusion: Postoperative complications and mortality was comparable in patients undergoing LPPG and LDG. Registration number: NCT02595086 (http://www.clinicaltrials.gov ). Abstract : A multicentre RCT (KLASS 04) comparing laparoscopic pylorus-preserving gastrectomy (LPPG) with laparoscopic distal gastrectomy (LDG) for middle third early gastric cancer showed that LPPG was comparable with LDG for short-term outcomes after surgery.